Functional Study of the circRNA_0006393/miR-375/IGFBP4 Axis in Fracture Healing Associated with Male Idiopathic Osteoporosis - Xiaoyi Guo; Jie Xu; Lin Chen; He Huang; Zewei Gao; Xijia Jiang (Journal of Investigative Surgery)
Background CircRNA_0006393 was reported to promote osteogenesis in glucocorticoid-induced osteoporosis, but its role in male idiopathic osteoporosis (MIO) has not been revealed.Aim To explore circRNA_0006393’s role in MIO.Methods Dual-luciferase reporter assay was performed to notarize the direct connection among circRNA_0006393, miR-375 and IGFBP4. Their value as biomarkers of MIO was confirmed by the ROC curve. The osteogenic induction was measured by detecting the ALP activity/expression and OCN/RUNX2 expression. The osteoclastic induction was evaluated by detecting TRAP activity and bone resorption capacity. The concentration of Fe2+, GSH, and ROS was detected to evaluate ferroptosis.Results MiR-375 was overexpressed in MIO patients, while circRNA_000639 and IGFBP4 presented low expression. CircRNA_0006393 promoted IGFBP4 expression by sponging miR-375. The AUC of circulating circRNA_0006393, miR-375, IGFBP4, or their combination in distinguishing unhealing and healing individuals with MIO-related fracture was 0.840, 0.851, 0.743, 0.960, respectively. CircRNA_0006393 reduced the ferroptosis process by regulating miR-375/IGFBP4. Iron overload inhibited the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSC) and promoted the osteoclastic differentiation of bone marrow-derived macrophage cells (BMMC).Conclusion CircRNA_000639 inhibited ferroptosis by regulating the miR-375/IGFBP4 axis, thereby promoting osteogenesis and hindering osteoclastic differentiation, and they are the biomarkers for MIO-related fracture healing.